Aplikasi Lubang Resapan Biopori Berkompos terhadap Peningkatan Fosfor pada Agroekosistem Kebun Kopi Robusta - Soemarno Soemarno; Yusuf Mahardika Nurin; Dinda Mahartian Yunita; Atiqah Aulia Hanuf (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2021)
Sloping topography, clay textures and improper fertilizer application create a high risk of surface runoff and nutrient loss. Phosphorus occurs as an important nutrient in coffee beans. The objective of this research is to analyze the effects of biopore infiltration hole with compost (BIHC) on the total and available phosphorus in robusta coffee in Bangelan plantation, Malang. A complete randomized block design with 4 replications was applied and the treatments consisted of control and BIHC. The BIHC process involved biopore hole depth of 30 and 60 cm for the goat manure and coffee pulp compost, respectively. Several parameters were also observed, including pH, total and available phosphorus as well as soil organic carbon (SOC) between 0-20, 20-40 and 40-60 cm in soil depth. Subsequently, the analysis of variance (ANOVA) and Duncan's Multiple Range Test (DMRT) were used to comprehend the data. The results showed the ability of BIHC to significantly increase the pH, SOC and total-P, compared to the control with less available-P. These total-P improvements up to 103.27, 108.73 and 132.09% were reported at soil depths between 0-20, 20-40 and 40-60 cm, respectively, while available-P were possibly enhanced up to 77.59, 28.27 and 151.99% at corresponding depth ranges.